Penggunaan Teknologi Dalam Pengembangan Asesmen Pembelajaran Pendidikan Agama Islam - Ariza, Nurul; Afifah, Qorina Khoirul (Belajea: Jurnal Pendidikan Islam, 2024)
: Lack of time during class hours, overcapacity of participants in one class, and many students not doing honest self-assessment are obstacles in assessing PAI learning. These obstacles can occur due to several factors such as too many questions to be prepared, an assessment structure that is too complicated and the lack of understanding of educators about the concept of using assessment. This study reveals how technology can facilitate educators in an effective and efficient assessment process at this time. This research method uses a type of qualitative research with a library research method by collecting data from various literatures related to the use of technology in the development of PAI learning assessments. The results of the study are that technology can help educators in developing assessments of students in the cognitive, affective and psychomotor domains.Â  Technology can help educators make questions and quizzes easier and more efficient, can assess students' attitudes, interests, confidence, emotional aspects, and be able to assess students' practical abilities as well as correct weaknesses and improve students' skills in PAI learning. As for some technologies that can be used in cognitive assessment; Google Form, Kahoot, and Quizizz. While in affective assessment; WhatsApp, Instagram, Twitter, and other similar applications and in psychomotor assessment; Zoom, Microsoft Teams, and Google Meet.